Main strategies of internet-based Japanese language teaching and the associated risks : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Japanese at Massey University - Tretiakov, Takako (Massey University, 2000)
This study formulates two models of using Internet in classroom based Japanese language education. The models identified, the static model and the dynamic model, can be used in planning the strategy of introducing Internet as an educational medium in Japanese language classroom. Apart from elaborating the features of the models, and clarifying their relationships to recognized foreign/second language teaching approaches, we determine the risks, associated with Internet based Japanese language education and consider the ways to mitigate them. Our study is backed by 2 surveys, and by qualitative and quantitative analysis of Internet search engine data and of a database of teachers' beliefs data. This study may be of value to Japanese language teachers and learners, education administrators and to designers of CALL software.
Keywords: Japanese language; Computer network resources; Computer-assisted instruction; Study and teaching; Internet in education